ANALISIS TINDAK PIDANA ILLEGAL LOGGING DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS TANPA IZIN SAH - Sinaga, Hasudungan (IBLAM LAW REVIEW, 2022)
This study is entitled criminal act analysis of Illegal Logging in forest areas with special purpose without legal permission: Case Study Decision No. 141/Pid.B/Lh/2021 / Pn.Mii. With the formulation of the problem of how the application of material crime in Illegal Logging in forest areas with special purposes without legal permission and how the basis for the judge's consideration in Decision No. 141/Pid.B/Lh/2021 / Pn.Mii. Using normative juridical methods. Conclusion b. Based on decision number: 141 / Pid.B/LH/2021 / PN.Mii, accused Arman Alias Maman Bin H. Muhammad Jaya was found legally and convincingly guilty of committing a criminal offense in the forestry sector in accordance with alternative charges. In this case, the perpetrator is given a criminal sanction in the form of confinement/prison and is also subject to a fine in accordance with Article 82 paragraph (1) letter B Jo Article 12 letter b of the Indonesian Law No. 18 of 2013 on the Prevention and Eradication of forest destruction. In the verdict given by the panel of judges, the perpetrator was sentenced to imprisonment for 1 year and 4 months and a fine of Rp500, 000, 000.00. If the fine is not paid, it will be replaced by imprisonment for 1 month.